Relationship between the compressive and tensile strengths of lime-treated clay containing coconut fibres - Vivi Anggraini,; Kim Huat, Bujang; Asadi, Afshin; Nahazanan, Haslinda (University of Maribor, Faculty of Civil Engineering, Transportation Engineering and Architecture, 2015)
The effects of coconut fibre on the mechanical characteristics of lime-treated clay are investigated in this study. The lime-treated clay specimens were prepared with a variety of coconut-fibre contents, i.e., 0.5%, 1%, 1.5% and 2%, in terms of the weight of dry soil. The stabilized specimens were tested at 7, 28 and 90 days after the treatment in order to observe the evolution of the mechanical resistance with time. The results of the unconfined compressive strength tests were used to determine the relationships between the compressive strengths and the indirect tensile strengths of the stabilized soil. Furthermore, the optimum percentage of coconut fibre mixed in the soil/lime mixtures was 1% of the dry mass and reinforcement at 90 days increases the peak compressive strength and the indirect tensile strength. Coconut-fibre inclusion changes the brittle behaviour of the lime-treated clay soil to give it a more ductile character.